Catalytic Screening for 1,2-Diol Protection: A Saccharose-Derived Hydrothermal Carbon Showcases Enhanced Performance - Laura Moreno; Rosario Pardo-Botello; Carlos J. Durán-Valle; Marta Adame-Pereira; Pedro Cintas; Larrisa Chan; David Cantillo; Rafael Fernando Martínez (Applied Sciences)
A benchmarking study is reported on a series of modified carbocatalysts to efficiently promote the acetalization of 1,2-diols under heterogeneous conditions. Among the catalysts surveyed, a hydrothermal carbon generated from saccharose, a cheap, abundant, and biobased material, showed excellent performance when tested on two representative diols. All catalysts have been thoroughly characterized, focusing on surface acidity and composition. Optimal working parameters such as temperature and catalyst loading could be established. Remarkably, sonication improved the diol protection, which proceeded faster at 25 °C. The catalyst could be easily recycled and reused several times. In addition, the protocol was successfully translated from batch to continuous flow operation using a packed-bed reactor.